ПЛУРИЛИНГВИЗМОТ – НОВО ЛИЦЕ НА ЈАЗИЧНИОТ И КУЛТУРНИОТ ИДЕНТИТЕТ (Philological Studies, 2019)
Conditioned by the accelerated processes of globalization and homogenization, as a serious threat to the linguistic and cultural diversity in the world, the affirmation of plurilingualism is becoming a priority. Namely, plurilingualism is turning into a strategic determination of global and European linguistic policies, which has resulted into the adoption of various international acts regulating this socio-linguistic occurrence. Firstly, this paper will consider the essential determinations of several international acts, such as the Universal Declaration of Linguistic Rights (1996), the European Charter for Regional or Minority Languages (1992), and the European Charter on Plurilingualism (2005), which open horizons for a linguistic coexistence and peace in the world, and in Europe, in terms of the recognition of the rights of each linguistic community to realize itself through its own language in various areas of life.
Keywords: plurilingualism, international acts, linguistic rights, linguistic policies